Recognizing the factors influential on the representational space of children with emphasis on their drawings (Case study: educational spaces) - Reyhāne Nikravesh; Seyed Gholāmrezā Islāmi; Jāle Sabernejād; Abdolhossein Kalāntari (فصلنامه نوآوری‌های آموزشی, 2021)
The purpose of this study was to identify the physical and non-physical factors affecting the desired experience of primary school students in Isfahan’s educational spaces which is innovative in terms of the subject matter and the nature of children's lived experiences of attending in the educational spaces. The methodology of the present article was based on mixed-methods and the students' mental images and lived experiences have been obtained using design-drawing method and their drawings. Given the integration of the identifier and the subject of identification in this method, it could be considered a suitable way to represent and understand the lived experience of children. A total of 192 drawings were classified by open coding method and they were analyzed using exploratory factor analysis by SPSS software. The results indicated that five main factors affect the students' lived experience and mental image of the educational space. Based on their priority, these factors are as follows: 1. emphasis on the building legibility; 2. referring to various types of activities; 3. emphasis on the overall appearance of the building; 4. paying attention to the natural factors and outdoor space and 5. paying attention to the details of environmental-sensory stimuli.